Brain white matter fibre tracts: a review of functional neuro-oncological relevance - Voets, Natalie L.; Bartsch, Andreas J.; Plaha, Puneet (Journal of neurology, neurosurgery, and psychiatry, 2017)
State-of-the-art glioma treatment aims to maximise neuro-oncological benefit while minimising losses in quality of life. Optimising this balance remains hindered by our still limited understanding of information processing in the human brain. To help understand individual differences in functional outcomes following neuro-oncological treatment, we review mounting evidence demonstrating the fundamental role that white matter connections play in complex human behaviour. We focus on selected fibre tracts whose destruction is recognised to elicit predictable behavioural deficits and consider specific indications for non-invasive diffusion MRI tractography, the only existing method to map these fibre tracts in vivo, in the selection and planning of neuro-oncological treatments. Despite remaining challenges, longitudinal tract imaging, in combination with intraoperative testing and neuropsychological evaluation, offers unique opportunities to refine our understanding of human brain organisation in the quest to predict and ultimately reduce the quality of life burden of both surgical and non-surgical first-line neuro-oncological therapies.
Published online first 14 July 2017
Gesehen am 06.09.2018